Application of Image Analysis to Establish Potential Relationship between Intracellular Interaction and Cell Migration Behavior - Ahmed, Tanvir; Munir, Muhammad Shafiul; Ahmed, Shoeb (Dhaka University Journal of Applied Science and Engineering, 2023)
In order to predict the movement and behavior of important cellular components computational language-based image processing approach caters a lot more than the traditional approaches. In this study, a relation of PI3K protein activity during cell migration has been evaluated using MATLAB based custom coding as an image analysis tool. Cells were imaged under fluorescence microscope to detect the PI3-Kinase activity in tandem with the morphological changes. Several cell movement metrics were assessed, indicating protein activity localization. Different parametric analysis confirms that cell migration is essentially controlled by the peripheral activity rather than the overall cell activity. A quantitative relationship has been proposed as a function of high intensity region area, intensity, and angle of movement, which fit 85% of total cellular responses. Customized analysis at intracellular cellular level has the potential to reveal some fine detail that eventually could contribute to the research on the critical diseases like cancer. DUJASE Vol. 7(1) 72-81, 2022 (January)